Prognostic value of melanoma-associated antigen A9 in renal cell carcinoma. (August 2012) - Hatiboglu, Gencay; Pritsch, Maria; Macher-Goeppinger, Stephan; Zöller, Margot; Huber, Johannes; Haferkamp, Axel; Pahernik, Sascha; Wagener, Nina; Hohenfellner, Markus
Abstract Objective. The aim of this study was to evaluate the prognostic relevance of melanoma-associated antigen (MAGE) A9 in renal cell carcinoma (RCC). Material and methods. Immunohistochemical staining for MAGE A9 was evaluated in a tissue microarray containing 587 RCC tumour tissue samples. Nuclear MAGE A9 expression was reviewed using a semiquantitative score. Follow-up has been surveyed since 1990 in a prospectively conducted tumour database. The effect of MAGE A9 expression on cancer-specific survival (CSS) was assessed by univariate and multivariate Cox regression analyses. Subgroup analyses were performed for non-metastatic and metastatic disease. Results.Median age in all patients was 63.2 years, 354 patients were male and 233 female, and 108 patients had metastatic disease. Median follow-up was 5.6 years for all patients and 9.0 years for patients still alive (range 0–19.9 years). High nuclear MAGE A9 expression was present in 326 tumour specimens (55.5%). In multivariate analyses high nuclear MAGE A9 expression was associated with poor CSS (p = 0.0027). Furthermore, tumour stage, lymph-node and distant metastasis, Fuhrman grade G3/4, Karnofsky index < 80% and male gender were associated with poor CSS. In subgroup analyses, results were concordant for patients with non-metastatic disease. In patients with metastatic disease, only Karnofsky index > 80% was a significant predictor for CSS; MAGE A9 expression could not be shown to be associated with CSS (p = 0.161). Conclusions.High nuclear MAGE A9 expression is independently associated with poor CSS in patients with non-metastatic RCC. The assessment of MAGE A9 expression can provide additional prognostic information and should be used in decision-making regarding adjuvant therapy in patients with non-metastatic disease.